Describing Return to Work after Stroke: A Feasibility Trial of 12-month Outcomes - Kathryn Radford; Mary I. Grant; Emma J Sinclair; Jade Kettlewell; Connor Watkin (Journal of Rehabilitation Medicine, 2020)

(untitled)
Objective: Stroke is the greatest cause of disability in adults. A quarter of strokes affect people of working age, yet under half return to work after stroke. There has been little investigation into what constitutes “return to work” following stroke. The aim of this study is to describe the work metrics of stroke survivor participants in a feasibility randomized controlled trial of an early stroke-specific vocational rehabilitation intervention. Methods: Retrospective analysis of trial data. Metrics on work status, working hours, workplace accommodations and costs were extracted from trial outcomes gathered by postal questionnaire at 3, 6, and 12 months’ post-randomization for 46 stroke participants in a feasibility randomized controlled trial. Participants were randomized to receive vocational rehabilitation (intervention) or usual care (control). Results: Two-thirds (n = 29; 63%) of participants returned to work at some point in the 12 months following stroke. Participants took a mean of 90 days to return to work. Most returned to the same role with an existing employer. Only one-third of participants who were employed full-time at stroke onset were working full-time at 12 months post-stroke. Most participants experienced a reduction in pre-stroke earnings. Workplace accommodations were more common among intervention group participants. More intervention participants than control participants reported satisfaction with work at both 6 and 12 months post-randomization. Conclusion: This study illustrates the heterogeneous nature of return to work and the dramatic impact of stroke on work status, working hours and income. Longitudinal research should explore the socioeconomic legacy of stroke and include clear definitions of work and accurate measures of working hours and income from all sources.